Polyurethane resin and fiber reinforced composite material and preparation method and application thereof

The low-activity polyurethane resin component is prepared by the prepolymer method, which solves the problems of short operable time and difficult process control of polyurethane resin in the existing technology, and achieves extending the resin operable time, reducing production costs and improving composite material performance. effect.

CN117924651BActive Publication Date: 2025-01-24南京聚发新材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410111733.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2025-01-24
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

The existing polyurethane resins have short operating time in composite materials production, difficult process control, and must be equipped with special two-component glue injection equipment, which increases production costs and environmental risks.

Method used

The prepolymer method is used to consume part of the isocyanate and isocyanate reactant groups through pre-reaction, introduce acrylate monomers to adjust the viscosity, prepare low-activity isocyanate components and reactant components, and extend the heat generation and gel curing time of the resin. .

Benefits of technology

It extends the operability time of polyurethane resin, reduces process technology difficulty and production costs, reduces resin waste generation and foaming risks, and improves the fiber content and mechanical properties of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117924651B_ABST
    Figure CN117924651B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a two-component polyurethane resin and a fiber-reinforced composite material suitable for a variety of composite material production processes and their application. By separately preparing two low-activity polyurethane resin components, and then mixing the two to form a resin and prepare a fiber-reinforced composite material, not only is the viscosity of the resin component controllable and not easy to foam, but the operating time of resin heating and gel curing is greatly extended, the application field is broadened, and the problems of existing polyurethane resins with short operating time, limited application process, and the need for supporting special glue injection equipment are solved. Furthermore, the performance of fiber-reinforced composite products prepared using the resin provided by the present invention is improved compared with existing resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer synthesis and preparation and application of fiber-reinforced composite materials, and in particular relates to a two-component polyurethane resin, a fiber-reinforced composite material using the resin, and a preparation method and application thereof. Background Art

[0002] In the prior art, the resins used in manufacturing fiber-reinforced composite materials mainly include epoxy resin, unsaturated polyester resin, vinyl resin, phenolic resin, etc. These resins have large supply and stable process technology, but they also have various problems. For example, the curing efficiency of epoxy resin is low, the unsaturated resin, vinyl resin and phenolic resin are brittle, and the mechanical properties are difficult to improve. In addition, there are serious environmental problems due to the large amount of styrene and formaldehyde substances used.

[0003] As polyurethane resins are gradually widely used in the field of composite materials, the above problems have been greatly improved. Polyurethane resins have high curing efficiency, and the production efficiency of the same pultrusion process can reach twice that of epoxy resins; polyurethane resins do not contain any organic solvents, and in processes such as winding that require the resin to be completely exposed to the air, there is no unpleasant odor in the workshop, and the product VOC is extremely low, showing good environmental protection; in addition, the overall mechanical properties of polyurethane-based composite materials are also 8% to 10% higher than traditional products. Based on this, the industry is very optimistic about the application prospects of polyurethane resins in the field of composite materials, and has successively issued a series of standards, such as GB / T 41491-2022 "Composite poles and towers for distribution networks", JT / T 1034-2016 "Polyurethane composite cable trays for highways", JT / T571-2019 "Glass fiber reinforced polyurethane energy-saving doors and windows", T / CECS10019-2019 "Polyurethane pultruded composite support system", etc.

[0004] The polyurethane produced by the existing technology mainly adopts a two-component mixing method, such as U.S. Patent US20040081830A1, Chinese Patent CN201080054523.4, Chinese Patent CN201510795935.8, Chinese Patent CN202180049615.1, etc.

[0005] There are usually two technical routes for the two-component mixing method. In the first, component A contains an active hydrogen compound or a mixture of active hydrogen compounds, as well as a catalyst, a cross-linking agent, a surfactant, a flame retardant, a plasticizer, a filler, etc.; component B is an isocyanate component composed of a polyisocyanate. In the second, component A contains an active hydrogen compound or a mixture of active hydrogen compounds, as well as a catalyst, a cross-linking agent, a surfactant, a flame retardant, a plasticizer, a filler, etc.; component B is a diisocyanate formed by the reaction of a part of the polyisocyanate with an active hydrogen compound.

[0006] The raw materials for synthesizing polyurethane resins are mostly commercial isocyanate components that can be directly purchased, such as polyphenylmethane polyisocyanate, which is a mixture of polypropylene oxide polyols supplemented with catalysts, release agents and other additives as the isocyanate reactant component. The two components are stored separately when not mixed. After the two-component resins are mixed, they are extremely active and have a short operating time. The resin heats up and thickens for only about 3 to 5 minutes, and the gel curing time is only about 5 to 30 minutes, which greatly limits the application of polyurethane resins in traditional composite materials technology. In order to adapt to the characteristics of polyurethane resins, companies must purchase and install special two-component injection equipment. During production, the two components of the resin are stored separately in the two material tanks of the two-component injection equipment. The equipment flow is adjusted according to production needs so that the two components of the polyurethane resin are mixed online and immediately heated and cured.

[0007] The existing two-component polyurethane mixing method for composite material production has the following disadvantages: it must be equipped with a dedicated two-component injection equipment, which increases the production cost; the operation time is short, which increases the technical difficulty of process control; if the two components are not used up after mixing, they will solidify and become waste, which increases the production cost of the enterprise; it is sensitive to moisture, causing the resin to foam easily, thereby reducing the strength of the final composite material. In addition, the fiber content of the composite material produced by the existing technology is difficult to increase, which affects the further optimization of product performance. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention adopts a "prepolymer" method, in which a low-activity isocyanate component and an isocyanate reactant component are prepared respectively by consuming part of the isocyanate and isocyanate reactant groups through pre-reaction and introducing acrylic monomers to adjust the viscosity. Not only is the viscosity of the resin component controllable and not easy to foam, but the operating time of the resin heating and gel curing is also greatly extended, thereby broadening the application field.

[0009] The present invention aims to provide a polyurethane resin and a fiber-reinforced composite material and a preparation method and application thereof, so as to solve the problems that the existing polyurethane resin has a short operating time, limited application process, and must be equipped with special glue injection equipment.

[0010] First, the present invention provides a polyurethane resin, including a component B and a component A, wherein the component B contains a reactive isocyanate group (-N=C=O), and the component A contains a hydroxyl group (-OH) having an active hydrogen atom that can chemically react with the isocyanate group in the component B, and the polyurethane resin is formed by mixing the component B and the component A.

[0011] Secondly, the present invention also provides a method for preparing the polyurethane resin as described above, comprising the following steps:

[0012] Step S1: preparation and synthesis of component B;

[0013] The weight ratio of raw materials of component B is as follows:

[0014]

[0015] The synthesis process is as follows: the first polymer diol from which water has been removed by vacuum is heated to 60-90°C, and the first isocyanate compound is added in a ratio of isocyanate to hydroxyl group of ≥2:1, and the reaction is performed for 2-4 hours to obtain an intermediate C; then, an initiator and a heat aging protection agent are added according to the ratio, and the mixture is stirred evenly, and the mixture is cooled to 60°C and discharged to obtain component B; wherein the intermediate C is an isocyanate-terminated prepolymer;

[0016] Step S2: Preparation and synthesis of component A;

[0017] The weight ratio of raw materials of component A is as follows:

[0018]

[0019] Synthesis process flow: the second polymer diol from which water has been removed by vacuum is heated to 60-90°C, and the second isocyanate compound is added in a ratio of isocyanate to hydroxyl group molar ratio ≥2:1, and the reaction is carried out for 2-4 hours to obtain intermediate D; unsaturated monoalcohol is continued to be added, and the reaction is carried out for 4-6 hours to obtain intermediate E; then, according to the proportion, the polymer polyol, accelerator, stabilizer, release agent, anti-light aging aid, and anti-hydrolysis aid in the formula are added, and stirred for 1 hour. After mixing evenly, the temperature is lowered to 40°C and the material is discharged to obtain component A; wherein, the intermediate D is a terminal isocyanate prepolymer; the intermediate E is an unsaturated double bond-terminated polyurethane polymer;

[0020] Step S3: mixing component B with component A;

[0021] The component B obtained in step S1 and the component A obtained in step S2 are mixed in a ratio of isocyanate mole number: hydroxyl mole number = 1:1. The mixing process depends on the production process. Mechanical weighing and stirring or metering pump discharging and connecting to a static mixer can be used for mixing. After the AB components are evenly mixed, the polyurethane resin is obtained.

[0022] Preferably, in step S1, the first isocyanate compound is one or a mixture of 4,4-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, toluene diisocyanate, toluene diisocyanate trimer, isophorone diisocyanate, isophorone diisocyanate trimer, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and dicyclohexylmethane diisocyanate.

[0023] Preferably, in step S1, the first polymer diol is a polyether diol with a molar mass of 200 to 2000 g / mol; or a polyester diol with a molar mass of 200 to 2000 g / mol; wherein the polyether diol is selected from one of polypropylene oxide ether diol, polyethylene oxide ether diol, and polytetramethylene oxide ether diol; and the polyester diol satisfies the following general formula:

[0024]

[0025] Among them, R 1 For benzene ring or C 4 -C 10 One of the saturated fatty carbon chains; R 2 C 2 -C 6 One of them.

[0026] Preferably, in step S1, the initiator is one or more of tert-butyl perbenzoate, benzoyl peroxide, diisopropyl peroxide, diisopropyl peroxydicarbonate, and azobisisobutyronitrile; the anti-heat aging aid is selected from one of hindered phenol antioxidants 1010, 1076 and phosphite antioxidant 168.

[0027] Preferably, in step S2, the second isocyanate compound is one or a mixture of 4,4-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, toluene diisocyanate, toluene diisocyanate trimer, isophorone diisocyanate, isophorone diisocyanate trimer, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and dicyclohexylmethane diisocyanate.

[0028] Preferably, in step S2, the second polymer diol is a polyether diol with a molar mass of 200 to 1000 g / mol; or a polyester diol with a molar mass of 200 to 1000 g / mol; wherein the polyether diol is selected from one of polypropylene oxide ether diol, polyethylene oxide ether diol, and polytetramethylene oxide ether diol; and the polyester diol conforms to the following general formula:

[0029]

[0030] Among them, R 3 For benzene ring or C 4 -C 10 One of the saturated fatty carbon chains; R 4 C 2 -C 6 One of them.

[0031] Preferably, in step S2, the unsaturated monoalcohol is one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and allyl polyoxypropylene ether having a molar mass of 1200 g / mol.

[0032] Preferably, in step S2, the polymer polyol is selected from one or a mixture of polyether polyols or polyester polyols with an average functionality of 2 to 6; wherein the polyether polyol is one of polypropylene oxide ether polyol, polyethylene oxide ether polyol and polytetramethylene oxide ether polyol; and the polyester polyol is one of polycaprolactone diol, polycaprolactone triol and polycaprolactone tetraol.

[0033] Preferably, in step S2, the accelerator is selected from one of zinc cyclopentaneate, zinc isooctanoate, cobalt cyclopentaneate, cobalt isooctanoate, copper cyclopentaneate, and copper isooctanoate; the stabilizer is selected from one of 2,4-pentanedione, 2,4-hexanedione, 2,4-octanedione, 3,5-octanedione, diethanol succinate, dipropylene glycol succinate, and dibutyl succinate; the release agent is selected from one of 1948mch from Axel Company of the United States and 550D from Revos Company of Germany; the anti-light aging agent is selected from one of B75 from BASF Company of Germany and 2195MK from Changzhou Xince Company; the anti-hydrolysis agent is Hostavin N30 from Klein Company of the United States.

[0034] Thirdly, the present invention also provides a method for preparing a fiber-reinforced composite material using the polyurethane resin as described above, comprising the following steps:

[0035] S11: selecting polyurethane resin and reinforcing fiber as raw materials, wherein the polyurethane resin is component B and component A obtained in steps S1 and S2 respectively, and the reinforcing fiber is one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and polyester fiber;

[0036] S12: Component B and component A are mixed in a ratio of isocyanate mole number: hydroxyl mole number = 1:1. Depending on the product manufacturing process, the components can be mixed by weighing, mechanical stirring, or by pumping out a feed pump connected to a static mixer to obtain a polyurethane resin after mixing.

[0037] S13: Depending on the application scenario, different reinforcing fibers are selected. According to the production equipment, pultrusion process, winding process, hand lay-up process, wet molding process, sheet molding compound or prepreg molding process are selected to prepare fiber-reinforced composite materials.

[0038] Preferably, in step S12, the component A and the component B are mixed and poured into an open glue tank without the need for special glue injection equipment.

[0039] Fourth, the present invention also provides the application of the fiber reinforced composite material obtained by the preparation method as described above, which can be widely used in wind turbine blade beams, door and window profiles, highway bridges, solar photovoltaic frames and brackets, train floor strips, offshore aquaculture plank roads including pultrusion process; or power grid poles, communication towers, seawater desalination pipelines and urban underground pipelines in winding process; or front and rear edge and web reinforcement of wind turbine blades and FRP troughs in hand lay-up process; or special-shaped parts for new energy vehicles in wet molding process; or sheet molding compounds and prepregs for pressing large special-shaped materials.

[0040] Compared with the prior art, the technical effects of the present invention are as follows:

[0041] (1) The present invention relates to a method for preparing and using a polyurethane resin and a fiber-reinforced composite material, which has the following advantages: (a) good environmental performance. The resin of the present invention does not contain styrene, formaldehyde, small molecule ammonia and other volatile and odorous small molecules. The VOC is extremely low during the production and use of the composite material, and is harmless to personnel and the environment. (b) The performance is significantly improved. The composite material of the present invention is a polyurethane resin-based composite material. After the polyurethane resin is cured, in addition to the mechanical properties brought by the highly cross-linked polymer molecular chains, the large number of hydrogen bonds formed by the carbamate itself further enhance the mechanical strength and toughness, and give the final composite material product excellent transverse (90° direction) mechanical properties. This is also the reason why the polyurethane resin can be prepared by the pultrusion process. (c) High fiber content. Compared with the composite materials with fiber content of 78%-80% such as traditional unsaturated resin, vinyl resin and epoxy resin, the fiber content of polyurethane resin-based composite materials can reach 83%, which not only improves the mechanical properties of composite products, but also further reduces the raw material cost of composite materials; (d) The resin has good processability. The NCO% content of the polyurethane resin B component prepared by the present invention is low, which not only reduces the sensitivity to moisture and is not easy to foam, but also greatly improves the operating time of the resin, so that the traditional matching special glue injection equipment to meet the resin mixing and use is changed to the process of batch mixing with open glue tank.

[0042] (2) Compared with the two-component polyurethane resin currently used, the method of the present invention has the following advantages: the operating time is greatly extended. On the one hand, the composite material production line can be simplified. There is no need to use the two-component glue injection system that must be used in the existing polyurethane-based composite material production line. The resin can be mixed through the open glue tank of the traditional process, which greatly reduces the process technology difficulty and production cost. On the other hand, the applicable process range of the resin is broadened. After mixing, the resin of the present invention can be put into use immediately, pre-mixed with reinforcing fibers through pultrusion, winding, hand lay-up, wet molding, sheet molding compound, and then cured by heating to complete the reaction of isocyanate with isocyanate reactants and the cross-linking reaction between the double bonds of unsaturated monoalcohols in sequence; it can also be left to stand at room temperature overnight, first slowly completing the reaction of isocyanate with isocyanate reactants in the resin to form a solid resin that can be heated and melted. At this time, the solid resin still contains a large amount of unreacted unsaturated double bonds. When in use, the solid resin is heated and melted, impregnated with continuous fiber cloth, and cooled to obtain a prepreg cloth, which can be heated and cured by a molding process.

[0043] (3) Compared with unsaturated resins, vinyl resins and phenolic resins, the resins and finished composite materials of the present invention are very environmentally friendly during production, without any unpleasant odor or small molecules harmful to the environment and health; compared with epoxy resins, the resins of the present invention are highly active and have high production efficiency for finished composite materials; compared with traditional polyurethane resins that have a short gel time and require special two-component injection equipment, the resins of the present invention have a long operation time, and therefore, no new equipment is required, and the traditional process is not changed, and the existing equipment can be directly used. Finally, the fiber-reinforced composite material products prepared using the resins provided by the present invention have improved performance compared to existing resins. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 : Testing site of the wound pole prepared by the resin of the present invention.

[0045] Figure 2 : Comparison of load performance of wound poles prepared with different resins.

[0046] Figure 3 : a / b is the bond between the resin and the fiber of the present invention; c / d is the SEM electron microscope photo of the bond between the resin and the fiber at the fracture point of the load test. DETAILED DESCRIPTION

[0047] Exemplary embodiments of the present invention are described in detail below. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments can be implemented and various changes can be made to the present invention without departing from the spirit and scope of the present invention. The principles and features of the present invention are described below in conjunction with the accompanying drawings and specific embodiments, and the examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If specific techniques and reaction conditions are not indicated in the embodiments, the techniques or conditions or product specifications described in the literature in this area can be carried out. All reagents, instruments or equipment that do not indicate the manufacturer can be obtained commercially.

[0048] Example 1 Synthesis of polyurethane resin and preparation and testing of flat plate under pultrusion process

[0049] Step 1, synthesis and preparation of component B:

[0050] Process flow: 400kg of the first polymer diol polypropylene oxide ether diol (molar mass of 2000g / mol) from which water has been removed in vacuum is heated to 90°C, and 50kg of the first isocyanate compound 2,4-diphenylmethane diisocyanate and polyphenylmethane polyisocyanate are added in a molar ratio of isocyanate to hydroxyl group of 2:1, totaling 100kg. The reaction is carried out for 3h to obtain an intermediate C-terminal isocyanate-based prepolymer. According to the weight of the first isocyanate compound and the proportion, 15kg of diisopropyl peroxide initiator and 1kg of antioxidant 1010 are added, the mixture is stirred evenly, and the mixture is sealed and stored.

[0051] Step 2: Synthesis and preparation of component A:

[0052] Process flow: 20 kg of the second polymer diol polytetramethylene ether diol (molar mass 200 g / mol) which has been vacuum-dehydrated is heated to 60°C, and 77.8 kg of the second isocyanate compound toluene diisocyanate (5.4 kmol) and 22.2 kg of isophorone diisocyanate (1.0 kmol) are added in a ratio of 6.4:1 of the molar ratio of isocyanate to hydroxyl group, a total of 100 kg, and the reaction is carried out for 2 hours to obtain the intermediate D-terminal isocyanate prepolymer; 200 kg is added Hydroxypropyl methacrylate, continue to react for 6 hours to obtain the intermediate E unsaturated double-bond terminated polyurethane polymer; according to the weight of the second isocyanate compound and the proportion, continue to add 50kg of polymer polyol polycaprolactone tetraol with a functionality of 4 (molar mass 1000g / mol), 1.0kg of accelerator zinc isooctanoate, 1.0kg of stabilizer 2,4-octanedione, 15kg of release agent 1948mch, 5kg of German BASF B75 anti-light aging additive, and no hydrolysis resistance additive is added.

[0053] Step 3: Mix component B and component A evenly in a ratio of -NCO to -OH molar number 1:1, pour into the open glue tank of the pultrusion process production line, use continuous glass fiber and a three-stage mold, and the temperatures of the three zones of the mold are 120°C, 160°C, and 190°C respectively.

[0054] Step 4: Use crawler pultrusion equipment to prepare wind turbine blade beam plates. According to the actual production conditions, adjust the content of glass fiber to prepare products with the highest fiber content.

[0055] Comparative Example 1

[0056] Using the same production equipment and production method, unsaturated resin-based beam boards, vinyl resin-based beam boards, epoxy resin-based beam boards, and commercially available ordinary unmodified two-component polyurethane resin-based beam boards were prepared respectively. During the preparation, the content of glass fiber was adjusted according to the actual production conditions, and products with fiber content of 78% and 83% were prepared respectively, among which 78% fiber content was the higher value of the traditional resin use process, and 83% was the higher value of the polyurethane resin use process.

[0057] Table 1A. Comparison of the performance of the resin of the present invention and conventional resin pultrusion process

[0058]

[0059]

[0060] Table 1B. Comparison of pultrusion process performance test between the resin of the present invention and the unmodified polyurethane resin

[0061]

[0062] As can be seen from Table 1A, compared with traditional unsaturated resins, vinyl resins and epoxy resins, the resin of the present invention has more than 10% improvement in mechanical properties of the resin cured product and the composite material with 78% fiber content; the environmental protection is consistent with that of epoxy resin, and better than that of unsaturated resin and vinyl resin. The product has extremely low VOC and no odor, retaining the advantages of high performance and environmental protection of the polyurethane resin itself; the gel time is consistent with that of traditional resins. On this basis, the polyurethane resin pultrusion is successfully completed by using an open glue tank process, which greatly reduces the difficulty and cost of the preparation process of polyurethane resin-based composite materials.

[0063] As can be seen from Table 1B, compared with the common unmodified two-component polyurethane resin used in the mainstream industry, the modified two-component polyurethane resin prepared by the present invention has a longer gel time of more than 2 hours and a higher density of the resin solidified product. The analysis is that the isocyanate group in the unmodified polyurethane resin is sensitive to moisture in the air, resulting in the water absorption reaction inside the system to generate trace carbon dioxide, while the modified polyurethane resin of the present invention consumes part or most of the isocyanate group through the prepolymerization reaction in the preparation stage, thereby greatly reducing the sensitivity of the resin to moisture; the mechanical properties of the resin solidified board of the present invention and the performance of the composite material with the same fiber content of 83% are improved compared with the unmodified polyurethane resin. The reason for the analysis is that the long resin gel time is conducive to the discharge of air between the resin and the fiber, thereby reducing the preservation and generation of bubbles and microcracks inside the resin and the composite material. This conjecture also verifies the above-mentioned result that the density of the resin solidified product of the present invention is higher; in addition, since the open glue tank pultrusion is directly adopted, there is no need to use a matching glue injection equipment, and the resin of the present invention and the matching process reduce the production cost and process technology difficulty of the product; the remaining properties, including production processability and environmental protection, are basically the same as those of the unmodified polyurethane resin;

[0064] In summary, the modified two-component polyurethane resin of the present invention combines the advantages of low production cost of traditional resins and high mechanical and environmental performance of polyurethane resins, and can greatly improve the cost performance and competitiveness of products in the application fields provided by the present invention.

[0065] Example 2 Synthesis of polyurethane resin and preparation and testing of pipes under winding process

[0066] Step 1, synthesis and preparation of component B:

[0067] Process flow: Heat 100g of the first polymer diol polytetramethylene oxide diol (molar mass of 1000g / mol) from which water has been removed in vacuo to 60°C, add 100kg of the first isocyanate compound isophorone diisocyanate at a molar ratio of isocyanate to hydroxyl group of 4.5:1, react for 4h to obtain an intermediate C-terminal isocyanate prepolymer, add 10g of benzoyl peroxide initiator and 0.5kg of antioxidant 1076 according to the weight of the first isocyanate compound and the proportion, stir evenly, and seal for storage.

[0068] Step 2: Synthesis and preparation of component A:

[0069] Process flow: 100kg of the second polymer diol polybutylene adipate diol (molar mass 1000g / mol) from which water has been removed by vacuum is heated to 60°C, and 100kg of the second isocyanate compound hexamethylene diisocyanate trimer is added at a molar ratio of isocyanate to hydroxyl group of 2.7:1, and the reaction is carried out for 4 hours to obtain the intermediate D-terminal isocyanate prepolymer; 100kg of hydroxyethyl acrylate is continued to be added, and the reaction is continued for 4 hours to obtain the intermediate E unsaturated double-bond terminated polyurethane polymer; according to the weight of the second isocyanate compound and the proportion, 100kg of polymer polyol polypropylene oxide ether polyol (molar mass 600g / mol) with a functionality of 6 is continued to be added, 0.1kg of accelerator cobalt cyclohexaneate, 0.1kg of stabilizer 2,4-pentanedione, no release agent and anti-light aging agent are added, and 5kg of hydrolysis resistance agent Hostavin N30 of Klein Company, USA is added.

[0070] Step 3: Mix component B and component A evenly in a ratio of -NCO to -OH molar number 1:1, pour into the open glue tank of the winding process production line, and use continuous glass fiber, an outer diameter of 250mm, an inner diameter of 200mm, and a length of 12m for power grid poles. After winding, the curing conditions are 120℃, 2h.

[0071] Step 4: Use external curing winding equipment to prepare a cylindrical hollow pole tower. Adjust the content of glass fiber according to the actual production conditions.

[0072] Comparative Example 2

[0073] Using the same production equipment, conditions and processes, unsaturated resin-based poles, vinyl resin-based poles, epoxy resin-based poles and commercially available ordinary unmodified two-component polyurethane resin-based poles were prepared respectively. During preparation, the contents of glass fiber and resin were controlled to be basically the same according to the actual production conditions.

[0074] Table 2 Performance test of different resin winding processes

[0075]

[0076] The unmodified two-component polyurethane resin cannot complete the winding preparation of the entire pole because of its short operating time and severe foaming. Figure 1 To further compare the performance of the resin of the present invention, two polyurethane resins used in large quantities abroad were selected for comparison (RIMLINE resin from Huntsman and Elastilit resin from BASF). The load performance of the poles wound with different resins was compared. Figure 2 As shown, the microscopic bonding between fiber and resin is Figure 3 shown.

[0077] From Table 2, Figure 2 and Figure 3 It can be seen that the resin of the present invention has a long gel time, can be produced with an open glue tank, has low technical difficulty and is environmentally friendly. The pole tower load test results show that the load performance of the pole prepared by the resin prepared by the present invention is significantly better than that of the traditional resin, and is not lower than that of foreign products; the SEM electron microscope results show that the resin of the present invention is well infiltrated with the fiber, and the fiber and the resin at the break are not completely peeled off.

[0078] In addition, compared with the unmodified two-component polyurethane resin, the resin cured product of the present invention has a higher density, and the reason for analysis is similar to that of Example 1.

[0079] Example 3 Synthesis of polyurethane resin and preparation and testing of boards using hand lay-up process

[0080] Step 1, synthesis and preparation of component B:

[0081] Process flow: 20kg of the first polymer diol polyethylene terephthalate diol (molar mass of 200g / mol) from which water has been removed by vacuum is heated to 80°C, and 100kg of the first isocyanate compound toluene diisocyanate is added at a molar ratio of isocyanate to hydroxyl group of 2.9:1. The reaction is carried out for 2h to obtain an intermediate C-terminal isocyanate prepolymer. According to the weight of the first isocyanate compound and the proportion, 2kg of diisopropyl peroxide initiator and 0.1kg of antioxidant 168 are added, the mixture is stirred evenly, and the mixture is sealed and stored.

[0082] Step 2: Synthesis and preparation of component A:

[0083] Process flow: 40kg of the second polymer diol polypropylene oxide ether diol (molar mass 400g / mol) from which water has been removed by vacuum is heated to 70°C, and 100kg of the second isocyanate compound 4,4-diphenylmethane diisocyanate is added according to the molar ratio of isocyanate to hydroxyl group of 4:1, and the reaction is carried out for 3 hours to obtain the intermediate D-terminated isocyanate prepolymer; 150kg of hydroxyethyl methacrylate is continued to be added, and the reaction is continued for 5 hours to obtain the intermediate E unsaturated double-bond terminated polyurethane polymer; according to the weight of the second isocyanate compound and the proportion, 80kg of polymer polyol polyethylene oxide ether polyol (molar mass 800g / mol) with a functionality of 4 is continued to be added, 0.01kg of accelerator cobalt isooctanoate, 0.01kg of stabilizer diethanol succinic anhydride, no release agent is added, 3kg of anti-light aging aid B75, and 3kg of hydrolysis resistance aid Hostavin N30 of Klein Company, USA.

[0084] Step 3: Mix component B and component A evenly in a ratio of -NCO to -OH molar number 1:1, pour into an open glue tank, and use hand paste to achieve the impregnation of the resin and multi-layer polyester fiber cloth. After the impregnation is completed, the curing conditions are 75°C for 4h.

[0085] Step 4: Prepare 5 mm thick glass fiber cloth reinforced composite material by hand lay-up process. Adjust the glass fiber content according to the actual production conditions.

[0086] Comparative Example 3

[0087] Using the same production equipment, conditions and process, unsaturated resin-based hand lay-up composite material sheets, vinyl resin-based hand lay-up composite material sheets, and epoxy resin-based hand lay-up composite material sheets were prepared respectively. During preparation, the contents of polyester fiber and resin were controlled to be basically the same according to the actual production conditions.

[0088] Table 3 Test performance of different resin hand lay-up process boards

[0089]

[0090]

[0091] Unmodified two-component polyurethane resin is also not suitable for hand lay-up process due to the short gel time and foaming problem. As can be seen from Table 3, under the condition of consistent control of fiber content, the polyurethane resin of the present invention is consistent with the traditional resin in process and can be directly mixed in an open glue tank, but has obvious advantages in mechanical properties and environmental protection.

[0092] Example 4 Synthesis of polyurethane resin and preparation and testing of sheet materials under wet molding process

[0093] Step 1, synthesis and preparation of component B:

[0094] Process flow: Add 1.0kg of diisopropyl peroxydicarbonate to 100kg of dicyclohexylmethane diisocyanate, and then add 0.5kg of antioxidant 1010, stir evenly, and seal for storage.

[0095] Step 2: Synthesis and preparation of component A:

[0096] Process flow: 50kg of the second polymer diol polyoxyethylene ether diol (molar mass 1000g / mol) from which water has been removed by vacuum is heated to 70°C, and 100kg of the second isocyanate compound isophorone diisocyanate trimer is added at a molar ratio of isocyanate to hydroxyl group of 4.5:1, and the reaction is carried out for 4h to obtain intermediate D; 180kg of hydroxypropyl methacrylate is continued to be added, and the reaction is continued for 4.5h to obtain intermediate E; according to the weight of the second isocyanate compound and the proportion, 60kg of polymer polyol polytetrahydrofuran ether polyol (molar mass 1000g / mol) with a functionality of 2 is continued to be added, 0.5kg of accelerator copper cyclohexaneate, 0.5kg of stabilizer dibutyl succinic anhydride, 20kg of release agent 550D from German Revos, 1.5kg of anti-light aging agent 2915MK from Changzhou Xince, and 3.5kg of hydrolysis resistance additive Hostavin N30 from American Klein are added.

[0097] Step 3: Mix component B and component A evenly according to the ratio of -NCO and -OH molar number 1:1, pour into the molding mold, and heat to achieve the infiltration of the resin and the multi-layer basalt fiber cloth. After the infiltration is completed, the curing conditions are 135°C for 2 minutes.

[0098] Step 4: Prepare a 5 mm thick basalt fiber cloth reinforced composite material by wet molding process. Adjust the glass fiber content according to the actual production conditions.

[0099] Comparative Example 4

[0100] Using the same production equipment, conditions and process, unsaturated resin-based hand lay-up composite material sheet, vinyl resin-based hand lay-up composite material sheet, and epoxy resin-based hand lay-up composite material sheet were prepared respectively. During the preparation, the contents of glass fiber and resin were controlled to be basically the same as in Example 4 according to the actual production conditions.

[0101] Table 4 Test performance

[0102]

[0103] It can be seen from Table 4 that, under the condition of consistent fiber content control, compared with unmodified polyurethane, the polyurethane resin of the present invention is adjustable in viscosity and reactivity and can be applied to wet molding process. The process is consistent with traditional resins and can be directly mixed in an open glue tank, but compared with traditional resins, it has obvious advantages in mechanical properties and environmental protection.

[0104] Example 5 Synthesis of polyurethane resin and preparation and testing of sheet molding compound

[0105] Step 1, synthesis and preparation of component B:

[0106] Process flow: 40kg of the first polymer diol polyoxyethylene ether diol (molar mass of 400g / mol) from which water has been removed in vacuo is heated to 65°C, and 100kg of the first isocyanate compound dicyclohexylmethane diisocyanate is added at a molar ratio of isocyanate to hydroxyl group of 3.97:1. The reaction is carried out for 3.5h to obtain intermediate C. According to the weight of the first isocyanate compound and the proportion, 2.5kg of diisopropyl peroxide initiator and 2kg of azobisisobutyronitrile (a total of 4.5kg) and 0.2kg of antioxidant 1010 are added. The mixture is stirred evenly and sealed for storage.

[0107] Step 2: Synthesis and preparation of component A:

[0108] Process flow: 100kg of the second isocyanate compound hexamethylene diisocyanate and 120kg of allyl polypropylene oxide ether (Mn=1200g / mol) are reacted for 6 hours to obtain intermediate E; according to the weight of the second isocyanate compound and the proportion, 90kg of polymer polyol polycaprolactone polyol with a functionality of 3 (molar mass 300g / mol), 0.9kg of accelerator copper isooctanoate, 0.9kg of stabilizer dipropylene glycol succinic anhydride, 10kg of release agent 550D from Germany's Revos, 0.5kg of anti-light aging agent 2915MK from Changzhou Xin Ce, and 4.5kg of hydrolysis resistance additive Hostavin N30 from Klein Corporation of the United States are added.

[0109] Step 3: Evenly mix component B and component A in a ratio of -NCO to -OH molar number of 1:1, place in a mixing barrel, and use an SMC sheet molding compound manufacturing unit to prepare a polyurethane-based sheet molding compound, wherein the aramid staple fiber content is 30%, the calcium carbonate content is 30%, and the resin content is 40%.

[0110] Step 4: After the preparation is completed, the sheet is aged overnight at 50°C to obtain a stable polyurethane-based SMC sheet, and a 5mm thick sheet is pressed using a molding device for performance testing.

[0111] Comparative Example 5

[0112] Using the same production equipment, conditions and processes, unsaturated resin-based SMC, vinyl resin-based SMC sheets and epoxy resin-based SMC sheets with the same filler, fiber and resin content as in Example 5 were prepared respectively, and 5 mm thick panels were prepared using the same mold and press for testing.

[0113] Table 5 Performance test of different resin sheet molding compounds

[0114]

[0115] As can be seen from Table 5, the two components of the resin of the present invention can be naturally thickened and made into sheet molding compound after mixing, the viscosity becomes smaller and fluid at high temperature, and can be further cured and formed under the action of the initiator, which has a similar effect to the classic magnesium oxide thickening unsaturated resin, and the mechanical properties and environmental protection properties are significantly improved compared with the unsaturated resin. This formula solves the industry problem that traditional polyurethane resin cannot prepare sheet molding compound.

[0116] Example 6 Synthesis of polyurethane resin and preparation and testing of prepreg

[0117] Step 1, synthesis and preparation of component B:

[0118] Process flow: 300 kg of the first polymer diol polybutylene terephthalate diol (molar mass of 1500 g / mol) from which water has been removed by vacuum is heated to 65°C, and 100 kg of the first isocyanate compound 4,4-diphenylmethane diisocyanate is added in a molar ratio of isocyanate to hydroxyl group of 2:1. The reaction is carried out for 2 hours to obtain intermediate C. According to the weight of the first isocyanate compound and the proportion, 12.5 kg of tert-butyl perbenzoate initiator and 0.9 kg of antioxidant 168 are added. The mixture is stirred evenly and sealed for storage.

[0119] Step 2: Synthesis and preparation of component A:

[0120] Process flow: 90kg of the second polymer diol polybutylene phthalate diol (molar mass 500g / mol) from which water has been removed by vacuum is heated to 70°C, and 100kg of the second isocyanate compound isophorone diisocyanate is added at a molar ratio of isocyanate to hydroxyl group of 2.5:1, and the reaction is carried out for 4 hours to obtain intermediate D; 144kg of hydroxypropyl methacrylate is continued to be added, and the reaction is continued for 6 hours to obtain intermediate E; according to the weight of the second isocyanate compound and the proportion, 70kg of polymer polyol polypropylene oxide ether polyol (molar mass 600g / mol) with a functionality of 5 is continued to be added, 0.35kg of accelerator zinc isooctanoate, 0.35g of stabilizer 2,4-pentanedione, 20kg of release agent 1948mch from AXEL Company of the United States, no anti-light aging agent is added, and 2.5kg of hydrolysis resistance aid Hostavin N30 from Klein Company of the United States is added.

[0121] Step 3: Mix component B and component A evenly in a ratio of -NCO to -OH molar number 1:1, place in a mixing barrel, and mature overnight at 50°C to obtain a dough-like resin. Use a prepreg manufacturing unit to prepare a polyurethane-based carbon fiber prepreg, in which the resin content is 65%.

[0122] Step 4: After the preparation is completed, a stable polyurethane-based prepreg is obtained, and a 5mm thick plate is pressed using a molding device for performance testing.

[0123] Comparative Example 6

[0124] Using the same production equipment, conditions and processes, vinyl resin-based prepregs and epoxy resin-based prepregs with the same fiber and resin content as in Example 6 were prepared respectively, and 2 mm thick plates were prepared using the same mold and press for testing.

[0125] Table 6 Performance test of different resin prepreg processes

[0126]

[0127]

[0128] As can be seen from Table 6, the two components of the resin of the present invention can be naturally thickened after mixing to obtain a dough-like temperature-sensitive resin, which becomes less viscous at medium and high temperatures and is in a liquid state. It is impregnated with a continuous fiber cloth under the rolling of the rubber roller of the prepreg manufacturing unit, and cooled to obtain a prepreg. When used, it can be further cured and formed by heating under the action of an initiator. After the resin of the present invention is made into a prepreg and cured, its mechanical properties and environmental protection properties are significantly improved compared to vinyl resins, and are close to classic epoxy resins, but the prepreg prepared by the present invention can be directly stored at room temperature, solving the industry problem that traditional epoxy resin prepregs must be stored at low temperatures.

[0129] Example 7

[0130] According to the operating steps described in Example 1 and the raw material ratios shown in Table 7, polyurethane resin and fiber-reinforced composite materials were prepared, and the resin tensile modulus (MPa) and fiber content (%) of the finished products were respectively tested.

[0131] Table 7 Example 7 Raw material ratio

[0132]

[0133]

[0134] Example 8

[0135] According to the operating steps described in Example 2 and the raw material ratios shown in Table 8, polyurethane resin and fiber-reinforced composite materials were prepared, and the resin tensile modulus (MPa) and fiber content (%) of the finished products were respectively tested.

[0136] Table 8 Example 8 Raw material ratio

[0137]

[0138] Example 9

[0139] According to the operating steps described in Example 3 and the raw material ratios shown in Table 9, polyurethane resin and fiber-reinforced composite materials were prepared, and the resin tensile modulus (MPa) and fiber content (%) of the finished products were respectively tested.

[0140] Table 9 Example 9 Raw material ratio

[0141]

[0142]

[0143] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a polyurethane resin, the polyurethane resin comprising a component B and a component A, wherein the component B contains a reactive isocyanate group (-N=C=O), and the component A contains a hydroxyl group (-OH) having an active hydrogen atom that can chemically react with the isocyanate group in the component B, the polyurethane resin is prepared by mixing the component B and the component A, characterized in that: The preparation method comprises the following steps: Step S1: preparation and synthesis of component B; The weight ratio of raw materials of component B is as follows: The synthesis process is as follows: the first polymer diol from which water has been removed by vacuum is heated to 60-90°C, and the first isocyanate compound is added in a ratio of isocyanate to hydroxyl group of ≥2:1, and the reaction is performed for 2-4 hours to obtain an intermediate C; then, an initiator and a heat aging protection agent are added according to the ratio, and the mixture is stirred evenly, and the mixture is cooled to 60°C and discharged to obtain component B; wherein the intermediate C is an isocyanate-terminated prepolymer; Step S2: Preparation and synthesis of component A; The weight ratio of raw materials of component A is as follows: Synthesis process flow: the second polymer diol from which water has been removed by vacuum is heated to 60-90°C, and the second isocyanate compound is added in a ratio of isocyanate to hydroxyl group molar ratio ≥2:1, and the reaction is carried out for 2-4 hours to obtain intermediate D; unsaturated monoalcohol is continued to be added, and the reaction is carried out for 4-6 hours to obtain intermediate E; then, according to the proportion, the polymer polyol, accelerator, stabilizer, release agent, anti-light aging aid, and anti-hydrolysis aid in the formula are added, and stirred for 1 hour. After mixing evenly, the temperature is lowered to 40°C and the material is discharged to obtain component A; wherein, the intermediate D is a terminal isocyanate prepolymer; the intermediate E is an unsaturated double bond-terminated polyurethane polymer; Step S3: mixing component B with component A; The component B obtained in step S1 and the component A obtained in step S2 are mixed in a ratio of isocyanate mole number: hydroxyl mole number = 1:

1. The mixing process is determined according to the production process. Mechanical weighing and stirring or metering pump discharging and connecting to a static mixer are used for mixing. After the A and B components are evenly mixed, the polyurethane resin is obtained.

2. The method for preparing a polyurethane resin according to claim 1, characterized in that: In step S1, the first isocyanate compound is one or a mixture of 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, toluene diisocyanate, toluene diisocyanate trimer, isophorone diisocyanate, isophorone diisocyanate trimer, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and dicyclohexylmethane diisocyanate.

3. The method for preparing a polyurethane resin according to claim 1, wherein: In step S1, the first polymer diol is a polyether diol with a molar mass of 200 to 2000 g / mol; or a polyester diol with a molar mass of 200 to 2000 g / mol; wherein the polyether diol is selected from one of polypropylene oxide ether diol, polyethylene oxide ether diol, and polytetramethylene oxide ether diol; and the polyester diol satisfies the following general formula: Wherein, R1 is a benzene ring or a C4-C 10 One of the saturated fatty carbon chains; R2 is one of C2-C6.

4. The method for preparing a polyurethane resin according to claim 1, wherein: In step S1, the initiator is one or more of tert-butyl perbenzoate, benzoyl peroxide, diisopropyl peroxide, diisopropyl peroxydicarbonate, and azobisisobutyronitrile; the anti-heat aging aid is selected from one of hindered phenol antioxidants 1010, 1076 and phosphite antioxidant 168.

5. The method for preparing a polyurethane resin according to claim 1, wherein: In step S2, the second isocyanate compound is one or a mixture of 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, toluene diisocyanate, toluene diisocyanate trimer, isophorone diisocyanate, isophorone diisocyanate trimer, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and dicyclohexylmethane diisocyanate.

6. The method for preparing a polyurethane resin according to claim 1, wherein: In step S2, the second polymer diol is a polyether diol with a molar mass of 200 to 1000 g / mol; or a polyester diol with a molar mass of 200 to 1000 g / mol; wherein the polyether diol is selected from one of polypropylene oxide ether diol, polyethylene oxide ether diol, and polytetramethylene oxide ether diol; and the polyester diol conforms to the following general formula: Wherein R3 is a benzene ring or a C4-C 10 One of the saturated fatty carbon chains; R4 is one of C2-C6.

7. The method for preparing a polyurethane resin according to claim 1, characterized in that: In step S2, the unsaturated monoalcohol is one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and allyl polyoxypropylene ether with a molar mass of 1200 g / mol.

8. The method for preparing a polyurethane resin according to claim 1, wherein: In step S2, the polymer polyol is selected from one or a mixture of polyether polyols or polyester polyols with an average functionality of 2 to 6; wherein the polyether polyol is one of polypropylene oxide ether polyol, polyethylene oxide ether polyol and polytetramethylene oxide ether polyol; and the polyester polyol is one of polycaprolactone diol, polycaprolactone triol and polycaprolactone tetraol.

9. The method for preparing a polyurethane resin according to claim 1, wherein: In step S2, the accelerator is selected from one of zinc cyclopentaneate, zinc isooctanoate, cobalt cyclopentaneate, cobalt isooctanoate, copper cyclopentaneate, and copper isooctanoate; the stabilizer is selected from one of 2,4-pentanedione, 2,4-hexanedione, 2,4-octanedione, 3,5-octanedione, diethanol succinate, dipropylene glycol succinate, and dibutyl succinate; the release agent is selected from one of 1948mch of Axel Company of the United States and 550D of Revos Company of Germany; the anti-light aging agent is selected from one of B75 of BASF Company of Germany and 2195MK of Changzhou Xince Company; the anti-hydrolysis agent is Hostavin N30 of Klein Company of the United States.

10. A method for preparing a fiber-reinforced composite material using the polyurethane resin obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The steps include: S11: selecting polyurethane resin and reinforcing fiber as raw materials, wherein the polyurethane resin is obtained by mixing component B and component A obtained in steps S1 and S2 respectively, and the reinforcing fiber is one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and polyester fiber; S12: Component B and component A are mixed in a ratio of isocyanate mole number: hydroxyl mole number = 1:1, and according to the product manufacturing process, the mixture is mixed by weighing, mechanical stirring or by pumping out a feed pump connected to a static mixer to obtain a polyurethane resin after mixing; S13: Depending on the application scenario, different reinforcing fibers are selected. According to the production equipment, pultrusion process, winding process, hand lay-up process, wet molding process, sheet molding compound or prepreg molding process are selected to prepare fiber-reinforced composite materials.

11. The method for preparing a fiber-reinforced composite material according to claim 10, characterized in that: In step S12, the component A and the component B are mixed and poured into an open glue tank without the need for special glue injection equipment.

12. Application of the fiber-reinforced composite material obtained by the preparation method according to claim 10, characterized in that: Used in wind turbine blade beams, door and window profiles, highway bridges, solar photovoltaic frames and brackets, train floor strips or offshore aquaculture plank roads through pultrusion; or power grid poles, communication towers, seawater desalination pipelines or urban underground pipelines through winding; or front and rear edge and web reinforcements or FRP troughs of wind turbine blades through hand lay-up; or special-shaped parts for new energy vehicles through wet molding; or sheet molding compounds or prepregs for pressing large special-shaped materials.

Citation Information

Patent Citations

  • Pultrusion resin system based on polyurethane

    CN102639314A

  • A polyurethane resin system and a method for preparing pultruded fiber composites thereon.

    CN106700015B

  • Polyurethane reactive system for pultrusion

    CN115916857A

  • Polyurethane system and application thereof

    US20040081830A1

  • Polyurethane acrylate composition and application thereof

    CN113583198A